Pengantar editorial MediaPsi 10 (2) 2024 - Akhrani, Lusy Asa (Universitas Brawijaya, 2024)
This introductory section highlights the contributions featured in this edition of MediaPsi. The 10(2) 2024 issue presents five articles written in Indonesian, showcasing scientific research conducted through both quantitative and qualitative approaches. These studies explore diverse life phenomena, addressing topics such as education, consumer behavior, post-traumatic experiences following parental divorce, and the role of social capital in multicultural societies. Life's events often evoke unique human responses, as ideal conditions are not always guaranteed. For instance, no individual chooses to experience the challenges of being a child affected by parental divorce, which can lead to post-traumatic growth. Similarly, children born with physical, mental, or intellectual limitations face unique hurdles, yet schools employing effective teaching models with dedicated, teachers grit can help unlock their potential. Another scenario involves students balancing education with employment. Those who demonstrate high levels of grit often develop greater mindfulness, enabling them to manage distractions and excel academically. Other articles examine the impact of technological advancements, such as the ease of online shopping, which has contributed to a rise in impulsive buying behaviors. Additionally, the dynamics of multicultural societies present both challenges and opportunities. While high diversity serves as valuable social capital, it also requires a collective commitment to fostering harmony among citizens. Ultimately, these studies underscore the importance of human agency in managing psychological states and behavioral choices amid varying life circumstances. The breadth of topics in this edition of MediaPsi aims to provide theoretical insights and practical contributions, paving the way for further research in the field.